Compensation method for digital image data - FENG, CHANG-YUNG; LIN, YIH-MING; LIN, HUNG-TSE (2006)
This invention relates to a compensation method for digital image data, for compensating the digital image data generated when the luminance of a tube is unstable, including using the luminance data of a reference white plate to generate several compensating gains to compensate the digital image data, wherein the method is executed by software in a computer.